A Large Cardiac Mass: Diagnosis of Caseous Mitral Annular Calcification and Determining Optimum Management Strategy - Emanuel A. Shapera; Afshin Karimi; Luis R. Castellanos (Case Reports in Medicine)
A 64-year-old woman with dizziness and blurry vision underwent an evaluation for a possible stroke with a head-neck CT scan and a transthoracic echocardiogram. The head-neck CT scan was unremarkable, but the echocardiogram was notable for a 2.0×2.3 cm heterogeneous echodensity attached to the mitral valve. After a transesophageal echocardiogram and chest CT scan, the mass was determined to be a caseous mitral annular calcification, CMAC. This entity is a rare variant of MAC with an estimated prevalence of 0.068%. Echocardiographic techniques can distinguish CMAC from other intracardiac masses such as tumor, cyst, or abscess. CMAC is associated with cerebrovascular accidents; however, optimal treatment is controversial given the rarity of this clinical finding. Management strategies should be tailored based on the patient’s presentation, risk factors, and overall clinical circumstances.